2007
DOI: 10.1016/j.ajog.2007.03.076
|View full text |Cite
|
Sign up to set email alerts
|

Does labeling prenatal screening test results as negative or positive affect a woman’s responses?

Abstract: Objective-We tested whether adding interpretive labels (e.g., "negative test") to prenatal genetic screening test results changes perceived risk and preferences for amniocentesis.Study Design-Women (N=1,688) completed a hypothetical pregnancy scenario via the Internet. We randomized participants into two groups: high (12.5/1000) risk of fetal chromosomal problems or low (2/1000) risk. After prenatal screening, estimated risk was identical (5/1000) for all participants, but results were provided either alone or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…Other research 22 has found that depicting statistical information in pictographs reduced medical patients' reliance on anecdotes when making decisions, and another study 23 found that evaluative labels (e.g, "normal," "positive") presented with prenatal screening test results were better able to influence risk perceptions and behavioral intentions than were numbers.…”
Section: Communicating Health Information: Simplicity and Framingmentioning
confidence: 97%
“…Other research 22 has found that depicting statistical information in pictographs reduced medical patients' reliance on anecdotes when making decisions, and another study 23 found that evaluative labels (e.g, "normal," "positive") presented with prenatal screening test results were better able to influence risk perceptions and behavioral intentions than were numbers.…”
Section: Communicating Health Information: Simplicity and Framingmentioning
confidence: 97%
“…Category labels may also assist decision makers by making options easier to evaluate; their power has long been recognized by social psychologists (e.g., Allport, 1954). Zikmund-Fisher, Fagerlin, Keeton, and Ubel (2007) harnessed this power by providing labels such as "normal" or "positive" to prenatal screening test results and found that they influenced risk perceptions and behavioral intentions more than numbers alone. Although information providers are sometimes reluctant to provide labels that categorize and provide an evaluation of the meaning of numeric information (whether due to a desire to allow consumers the freedom to assess the information, a concern about possible litigation, or companies that like to receive positive but not negative scores), it may be that the absence of such labels means that numeric information will not be used.…”
Section: Hypothesismentioning
confidence: 99%
“…Alternatively, evaluative categories could add, not just meaning, but affective meaning to numeric information (Zikmund-Fisher et al, 2007). Affect has been proposed as a key component in the construction of values and preferences (Kahneman, Schkade, & Sunstein, 1998;Loewenstein, Weber, Hsee, & Welch, 2001;Slovic et al, 2002).…”
Section: Hypothesismentioning
confidence: 99%
“…This approach has been used successfully in previous research. [125][126][127] Findings broadly indicate that comprehension of the information is improved, particularly for people with low numeracy. 128 Furthermore, the same study suggested that evaluative categories can increase deliberative processing of the numerical information.…”
Section: Numerical Informationmentioning
confidence: 85%
“…Numerical descriptors may also increase perceptions of risk and, as a result, may be more effective at altering behaviour than numerical information in isolation. 127 In line with current evidence, natural frequencies with the same denominator were used to present key numerical information. 129 …”
Section: Numerical Informationmentioning
confidence: 98%